1998
DOI: 10.1007/s002340050597
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar involvement in metabolic disorders: a pattern-recognition approach

Abstract: Inborn errors of metabolism can affect the cerebellum during development, maturation and later during life. We have established criteria for pattern recognition of cerebellar abnormalities in metabolic disorders. The abnormalities can be divided into four major groups: cerebellar hypoplasia (CH), hyperplasia, cerebellar atrophy (CA), cerebellar white matter abnormalities (WMA) or swelling, and involvement of the dentate nuclei (DN) or cerebellar cortex. CH can be an isolated typical finding, as in adenylsuccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…Several studies have been performed on brain MR imaging and histologic findings in metabolic disorders presenting during the neonatal period, 3,4,21,24,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] but cUS findings have only been described in individual case reports. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] cUS has the advantage that it is readily available on neonatal units when infants are admitted.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed on brain MR imaging and histologic findings in metabolic disorders presenting during the neonatal period, 3,4,21,24,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] but cUS findings have only been described in individual case reports. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] cUS has the advantage that it is readily available on neonatal units when infants are admitted.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published 10-year retrospective study on childhood onset cerebellar ataxia revealed that in the group with a known genetic diagnosis, mitochondrial disease was the most common cause of cerebellar atrophy (Al-Maawali et al 2012). Other studies on childhood ataxias also confirm that a mitochondrial etiology may be the leading cause of the disease (Ramaekers et al 1997;Steinlin et al 1998;Finsterer 2009;Boddaert et al 2010;Terracciano et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Acute neurological deterioration in children is often associated with increased plasma and cerebrospinal fluid concentrations of BCAA and BCKA (Riviello et al, 1991;Levin et al, 1993). Magnetic resonance imaging studies in children with MSUD have confirmed both white matter and neuronal injury, including extensive brain edema and pathological changes in the basal ganglia (Brismar et al, 1990;Steinlin et al, 1998). At the histopathological level, deficiencies in myelination of major tracts in the pons and spinal cord, widespread areas of spongy change in the white matter, focal areas of astrocytosis, and binucleated neurons have also been reported (Langenbeck, 1984).…”
Section: Introductionmentioning
confidence: 99%